Improved temperature-dependent ice refractive index compilation in the far-infrared spectrum - Wang,S; Ren,T; Yang,P; Saito,M; Brindley,HE (Geophysical Research Letters, 2024)
A new ice refractive index compilation is reported for a broad spectrum ranging from 0.0443 to 106 m, focusing on the pronounced temperature-dependence of ice optical properties in the far-infrared (far-IR) segment (15-100 µm). A sensitivity study assuming spherical particles shows that selecting ice refractive indices at 12 temperatures and 215 wavelengths in the far-IR region gives sufficient accuracy in interpolated refractive indices for developing a new ice crystal optical property database. Furthermore, we demonstrate the differences between the bulk single-scattering properties computed for hexagonal ice particles with this new compilation compared to a previous iteration at three far-IR wavelengths where substantial differences are noticed between the two ice refractive index compilations. We suggest that our new ice refractive index dataset will improve downstream light-scattering applications for upcoming far-IR satellite missions and allow robust modeling of outgoing longwave radiation (OLR) under ice cloud conditions.